Abordagem investigativa em aulas de Matemática: uma investigação com casos de ensino na formação de professores Investigative approach in mathematics classes: an investigation with cases of teaching in teacher training - da Silva, Denise Knorst; Costa, David Antonio (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Esse estudo é parte de uma pesquisa de doutorado cuja investigação é sobre os conhecimentos do professor em uma ação de Formação orientada por e para a abordagem investigativa em aulas de Matemática. O recorte considera a análise de uma prática com casos de ensino como instrumento pedagógico na Formação de Professores. Apresenta-se a proposta, com objetivos e características dos casos de ensino, descrevendo o seu desenvolvimento e apresentando reflexões e análises a luz da problemática: Que compreensões sobre a abordagem investigativa em aulas de Matemática são produzidas por professores em Formação mediante a análise de casos de ensino? Os resultados apontam para o potencial dos casos de ensino na compreensão da abordagem investigativa pelos docentes em Formação. This study is part of a doctoral research and investigates the knowledge of the teacher in a training action guided by and for the investigative approach in mathematics classes. The cut considers the analysis of results obtained in practice with teaching cases as a pedagogical tool in teacher training. In the methodological perspective of the research with narratives, the proposal is presented, detailing the objectives and characteristics of the teaching cases, describing its development and presenting reflections and analyzes in light of the problematic: What understandings about the investigative approach in mathematics classes are produced by teachers through training in case studies? The results point to the potential of teaching cases in the understanding of the investigative approach by the teachers in formation, since the analysis indicates reflections on: investigative task, mathematical activity and communication as dialogue, defined as elements that characterize the investigative approach.